2021
DOI: 10.1080/21623945.2021.1910155
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin promotes intervertebral disc degeneration by inducing IL-6 expression through the ERK/JNK/p38 signalling pathways

Abstract: Visfatin reportedly induces the expression of proinflammatory cytokines. Severe grades of intervertebral disc disease (IVDD) exhibit higher expression of visfatin than mild ones. However, the direct relationship between visfatin and IVDD remains to be elucidated. This study aimed to clarify whether stimulation of visfatin in IVDD is mediated by IL-6. To investigate the role of visfatin in IVDD, a rat model of anterior disc puncture was established by injecting visfatin or PBS using a 27gauge needle. Results re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…These core target proteins are involved in multiple signaling pathways such as inflammation, immunity, metabolism, and proliferation-related signaling pathways. Studies have confirmed that the process of IDD can be delayed by inhibiting the TNF- α -induced inflammatory response and reducing the expression of inflammatory cytokines, including IL-6 [ 44 , 45 ]. It is worth noting that TP53 was found to be potentially involved in the progression of IDD by analyzing the microarray datasets of GSE19943, GSE15227, and GSE34095 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…These core target proteins are involved in multiple signaling pathways such as inflammation, immunity, metabolism, and proliferation-related signaling pathways. Studies have confirmed that the process of IDD can be delayed by inhibiting the TNF- α -induced inflammatory response and reducing the expression of inflammatory cytokines, including IL-6 [ 44 , 45 ]. It is worth noting that TP53 was found to be potentially involved in the progression of IDD by analyzing the microarray datasets of GSE19943, GSE15227, and GSE34095 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 2 −ΔΔCt (Ct: cycle threshold) was used to analyze the mRNA level, see Table 1 for primer sequence. 19 , 20 …”
Section: Methodsmentioning
confidence: 99%
“…The 2 ÀΔΔCt (Ct: cycle threshold) was used to analyze the mRNA level, see Table 1 for primer sequence. 19,20 Hydroxyproline Detection HYP was detected in lung homogenate samples using HYP kit (Nanjing Jiancheng Bioengineering Institute). Samples were weighed and pH adjusted according to the manufacturer's instructions.…”
Section: Q-pcr (Quantitative Real Time Pcr) Analysismentioning
confidence: 99%
“…In contrast, the knockdown of visfatin expression or the use of inhibitors showed a decrease in cellular autophagy and a downregulation of autophagy-related protein expression ( 100 ). Similarly, a study modeled in rats to simulate severe IVDD and performed pathway analysis indicated that inhibition of visfatin protected the nucleus pulposus from degeneration and that focusing on epidural lipids and visfatin would be a potential therapeutic target to control the inflammation associated with IVDD ( 101 ).…”
Section: Molecular Mechanisms Of Fat Infiltration In Psmsmentioning
confidence: 99%